2018
DOI: 10.1002/jcp.27366
|View full text |Cite
|
Sign up to set email alerts
|

LINC01433 promotes hepatocellular carcinoma progression via modulating the miR‐1301/STAT3 axis

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to play significant roles in hepatocellular carcinoma (HCC) tumor progression. LINC01433 has been implicated in the progression of lung cancer. However, its biological role in HCC remains poorly understood. In our current study, we focused on the detailed mechanism of LINC01433 in HCC development. First, it was exhibited that LINC01433 was remarkably elevated in HCC cells, which indicated that LINC01433 was involved in HCC. Then, knockdown of LINC01433 was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…LINC01287/miR-298/STAT3 feedback loop modulates cell growth and the epithelial-to-mesenchymal transition in HCC [20]. LINC01433 facilitates the development of HCC by regulating the miR-1301/STAT3 axis [21]. Nevertheless, the role of FAM83A-AS1 in HCC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01287/miR-298/STAT3 feedback loop modulates cell growth and the epithelial-to-mesenchymal transition in HCC [20]. LINC01433 facilitates the development of HCC by regulating the miR-1301/STAT3 axis [21]. Nevertheless, the role of FAM83A-AS1 in HCC is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration and invasion were measured using a 24-well Transwell system (8 µm pore; Costar, Badhoevedorp, the Netherlands) by using Transwell assay based on a previous study. 9 rna isolation and quantitative reverse transcriptase Pcr (qrT-Pcr)…”
Section: Transwell Assaymentioning
confidence: 99%
“…An increasing amount of studies have demonstrated that lncRNAs play vital functions in various biological processes and are closely correlated with human diseases, including cancer 7. By participating in the regulation of cell proliferation, migration, invasion, and differentiation, lncRNAs could affect or suppress tumorigenesis 8,9. For example, lncRNA DUXAP8 promotes the progression of renal cell cancer 10.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, NNT-AS1 promoted bladder cancer cell proliferation by targeting miR-1301-3p/PODXL axis and activating Wnt pathway [13] . Besides, ABHD11-AS1 and LINC01433 upregulated STAT3 level by sponging miR-1301-3p and promoted tumor progression in papillary thyroid carcinoma and hepatocellular carcinoma, respectively [14,15] . Hence, the function of miR-1301-3p is needed to elucidate for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%